ปัจจัยที่มีผลต่อการเลือกซัพพลายเออร์สัญชาติจีนของสินค้าประเภท โถสุขภัณฑ์ ในจังหวัดสมุทรสาคร - เสถียรเดชากุล, อนุรุธ; นากามัทสึ, มณีกัญญา (Journal of Buddhist Education and Research (JBER), 2024)
This research aimed to study: 1) marketing mix and selection of a Chinese supplier; 2) to compare the selection of a Chinese supplier, classified by personal factors; and 3) to present the influence between marketing mix and selection of a Chinese supplier. This research employs a quantitative method. The tool of this research is a questionnaire. Probability sampling and simple random sampling were used to collect data from 320 people who made the decision to hire a Chinese supplier to manufacture bidet products in Samut Sakhon province. The statistics of this research are frequency, percentage, mean, standard deviation, t-test, F-test, and multiple regression analysis by enter method. The research revealed that: 1) marketing mix and selection of a Chinese supplier were at a high level with an average of 3.71 and 3.62 and a standard deviation of .267 and .350; 2) personal factors by position had an influence on the selection of a Chinese supplier to produce bidet products in Samut Sakhon province at a statistically significant level of .05; and 3) marketing mix factor had an influence on the selection of a Chinese supplier to produce bidet products in Samut Sakhon province by the value of R2=.263 or 26.30 percent.